2010
DOI: 10.1002/ajmg.a.33756
|View full text |Cite
|
Sign up to set email alerts
|

Whole gene duplication of the PQBP1 gene in syndrome resembling Renpenning

Abstract: Renpenning syndrome is a well-described X-linked condition associated with multiple congenital anomalies and intellectual disability [OMIM 309500]. Typical signs include microcephaly, dysmorphic features, short stature, small testes, and lean body build. Renpenning syndrome is caused by mutations in the polyglutamine binding protein 1 (PQBP1) gene. Missense mutations, insertions, deletions, and duplications within the gene have been well-described. We present a 47-year-old male with clinical features resemblin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Overexpression of PQBP1 is also deleterious, promoting neuronal cell death in mice (Okuda et al, 2003;Marubuchi et al, 2005), and impaired long-term memory and behavioral abnormalities in Drosophila (Yoshimura et al, 2006). A PQBP1 gene duplication has been found in a patient with Renpenning syndrome, in which the PQBP1 protein may be overexpressed (Flynn et al, 2011). All of these findings suggest that maintaining PQBP1 within a restricted concentration range is essential for its proper biological actions.…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of PQBP1 is also deleterious, promoting neuronal cell death in mice (Okuda et al, 2003;Marubuchi et al, 2005), and impaired long-term memory and behavioral abnormalities in Drosophila (Yoshimura et al, 2006). A PQBP1 gene duplication has been found in a patient with Renpenning syndrome, in which the PQBP1 protein may be overexpressed (Flynn et al, 2011). All of these findings suggest that maintaining PQBP1 within a restricted concentration range is essential for its proper biological actions.…”
Section: Introductionmentioning
confidence: 99%
“…We observed it in Patients 1 and 3, especially in the field of motor skills. In a male patient with recurrent Xp11.22p11.23 duplication, Flynn et al (2011) described regression in areas of speech, memory and recognition, furthermore, leading to aggressive behavior. Helm et al (2017) reported regression of development with co-occurrence of the onset of seizures in a 20 year-old male patient.…”
Section: Discussionmentioning
confidence: 99%
“…Non-recurrent duplications of 0, 3-55 Mb in size have been reported in addition to the recurrent form of about 4.5 Mb, therefore the genes involved in the individual patient's duplications may be quite different. Patients with this copy number alteration, which have become known so far, show surprisingly similar symptoms despite the variability in CNV size: the resulting symptoms do not correlate with size and gene content of the affected genomic regions (Giorda et al, 2009;Zou and Milunsky, 2009;Flynn et al, 2011;Arican et al, 2018).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Flynn et al reported duplication of the PQBP1 gene and a phenotype-like Renpenning鈥檚 syndrome in a patient [ 72 ]. SNP microarray analysis (500 K) of the patient showed a 4.7 Mb duplication at Xp11.22鈥損11.23, including the PQBP1 gene, which was further confirmed to be duplicated using Multiplex Ligation-dependent Probe Amplification (MLPA) [ 67 ].…”
Section: Human Gene Mutations and Intellectual Disabilitymentioning
confidence: 99%